2017
DOI: 10.1016/j.bbadis.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Catalase overexpression modulates metabolic parameters in a new ‘stress-less’ leptin-deficient mouse model

Abstract: Oxidative stress plays a key role in obesity by modifying the function of important biological molecules, thus altering obesogenic pathways such as glucose and lipid signaling. Catalase, is an important endogenous antioxidant enzyme that catabolizes hydrogen peroxide produced by the dismutation of superoxide. Recent studies have shown knockdown of catalase exacerbates insulin resistance and leads to obesity. We hypothesized that overexpressing catalase in an obese mouse will modulate obesogenic pathways and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 66 publications
3
19
0
Order By: Relevance
“…We hence generated the "Bob-Cat" stress-less mice model, a hybrid between catalase transgenic mice [Tg(CAT) ± ] [42] and leptin-deficient, obese mice (heterozygous JAX 000632, B6.Cg-Lep ob /J). We have earlier shown that this novel mouse model had lower redox stress and improved adipose function compared to the Ob/Ob phenotype (JAX 000632, B6.Cg-Lep ob /J) and expressed both human and mouse catalase [43].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We hence generated the "Bob-Cat" stress-less mice model, a hybrid between catalase transgenic mice [Tg(CAT) ± ] [42] and leptin-deficient, obese mice (heterozygous JAX 000632, B6.Cg-Lep ob /J). We have earlier shown that this novel mouse model had lower redox stress and improved adipose function compared to the Ob/Ob phenotype (JAX 000632, B6.Cg-Lep ob /J) and expressed both human and mouse catalase [43].…”
Section: Introductionmentioning
confidence: 92%
“…We hypothesized that modulating redox stress by altering endogenous antioxidant content (overexpression of catalase) and/or via dietary intervention will improve energy metabolism, adipose tissue function, and overall glucose and lipid homeostasis. To better understand the interplay between redox regulation and dietary intervention in improving energy balance and maintaining insulin sensitivity, we compared the redox effects of a high-fat lard diet (HFD) and a high-fat omega 3-enriched diet (OM3) in a catalase-overexpressing 'stress-less' mice model [43]. In this model, we previously showed the ubiquitous overexpression of catalase altered anthropometric parameters, overall energy metabolism, as well as adipose tissue function in both male and female mice compared to WT controls [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also shown that leptin replacement therapy significantly downregulated expression of NADPH oxidase in adipose tissue of leptin-deficient ob/ob mice [ 96 ], indicating a protective role of leptin at homeostatic levels. Moreover, leptin production was increased by overexpression of endogenous antioxidant enzyme, catalase that catabolizes hydrogen peroxide produced by the dismutation of superoxide, and it was correlated with improved energy expenditure and decreased inflammatory and oxidative stress markers in ob/ob mice [ 97 ]. The relationship between leptin and oxidative stress has been recently investigated in a mouse model of oxidative stress, demonstrating that increased Nrf2 signaling suppressed oxidative stress and improved leptin resistance in the hypothalamus [ 98 ].…”
Section: Leptin and Oxidative Stressmentioning
confidence: 99%
“…The role of catalase in adiposity is still controversial. On the one hand, catalase overexpression in fat inhibits adiposity [29]. On the other hand, knockout animals for catalase show different metabolic profiles according to the literature.…”
Section: Discussionmentioning
confidence: 99%